Inflammasome activation as a link between obesity and thyroid disorders: Implications for an integrated clinical management - Le Moli, Rosario; Vella, Veronica; Tumino, Dario; Piticchio, Tommaso; Naselli, Adriano; Belfiore, Antonino; Frasca, Francesco (Frontiers in Endocrinology, 2022)
Obesity is strongly associated with chronic low-grade inflammation. Obese patients have an increased risk to develop thyroid autoimmunity and to became hypothyroid, suggesting a pathogenetic link between obesity, inflammation and autoimmunity. Moreover, type 2 diabetes and dyslipidemia, also characterized by low-grade inflammation, were recently associated with more aggressive forms of Graves’ ophthalmopathy. The association between obesity and autoimmune thyroid disorders may also go in the opposite direction, as treating autoimmune hyper and hypothyroidism can lead to weight gain. In addition, restoration of euthyroidism by L-T4 replacement therapy is more challenging in obese athyreotic patients, as it is difficult to maintain thyrotropin stimulation hormone (TSH) values within the normal range. Intriguingly, pro-inflammatory cytokines decrease in obese patients after bariatric surgery along with TSH levels. Moreover, the risk of thyroid cancer is increased in patients with thyroid autoimmune disorders, and is also related to the degree of obesity and inflammation. Molecular studies have shown a relationship between the low-grade inflammation of obesity and the activity of intracellular multiprotein complexes typical of immune cells (inflammasomes). We will now highlight some clinical implications of inflammasome activation in the relationship between obesity and thyroid disease.